Pharmacological Potential and Mechanisms of Action Involved in Oil Species from the Brazilian Amazon: The Case of Abelmoschus esculentus L. Moench, Euterpe oleracea Martius and Bixa orellana Linné - Sales, Priscila Faimann; Koga, Rosemary de Carvalho Rocha; Souza, Agerdanio Andrade de; Nascimento, Aline Lopes do; Pinheiro, Fernanda Cavalcante; Alberto, Andressa Ketelem Meireles; Costa, Madson Jonhe da; Carvalho, José Carlos Tavares (Pharmacognosy Reviews)
The chemical versatility of vegetable oils, attributed to biological properties, constitutes great value for the economic, technological and nutritional sector, promoting the interest of these Amazonian natural resources. The oils present variations in their chemical composition, regarding the presence of fatty acids with promising biological properties. The species Abelmoschus esculentus L. Moench, Euterpe oleracea Martius and Bixa orellana Linné, have pharmacological activities. Although these species are the subject of many studies, most of the scientific information is not related to the use of their oils. Therefore, this study aimed to review the secondary metabolites of vegetable oils of these species with pharmacological potential, such as antihypercholesterolemic and mechanisms of action involved, aiming to make the use of oil from such species in the field of drug innovation opportune. Therefore, the research was carried out using the following databases: CAPES, PubMed, Science Direct (Elsevier), Springer-Nature, SciELO and Google Scholar journals, using keywords such as A. esculentus, E. oleracea, B. orellana, correlated with oils, seeds, secondary metabolites, fatty acids and mechanisms of action. The species showed great bioactive activity attributed to their oils, especially in the anti-hypercholesterolemic activity, which can be explained by several pathways of gene expression mechanisms such as the interaction of peroxisome proliferator-activated receptors (PPARs), hepatic X receptors (LXRs), hepatic nuclear factor-4 (HNF4) receptors and sterol regulatory element binding proteins (SREBPs) that act on lipid modulation. The species have great pharmacological potential, especially in view of the use of their vegetable oils against the modulation of metabolic disorders.
Keywords: Pharmacology; Phytochemistry; Oil; Fruits; Seeds